The Acupuncture Therapeutic Approach in Temporal Arteritis Vasculitis: A Case Report - Yılmaz Sezgin (Medical Association of Pharmacopuncture Institute, 2018)
Temporal arteritis is a form of vasculitis that involves the large- and medium-diameter arteries and leads to progressive headache. Symptoms may be accompanied by vision disorder, subfebrile temperature, fatigue, lack of appetite, weight loss, sweating, and joint pains. While cortisone therapy reduces the symptoms, its effects in terms of improving quality of life are limited. We opted to benefit from the effects of acupuncture to reduce symptoms and increase quality of life in a case of temporal arteritis, a chronic disease. A 75-year-old woman presented with pain on both sides of the head. The pain occurred in the form of agonizing attacks 2-3 times a week. Accompanying neck pain was present, together with continuous lethargy and fatigue. Physical examination revealed decreased cutaneous elasticity and muscle mass, and a depressive mood state was present. The patient was first administered six sessions of acupuncture therapy directed toward the migraine etiology. When no response was achieved, we investigated temporal and parietal region points associated with headache in the literature. Points GB1,8,18, ST8, SI19, and BL8 were added to the treatment. The pain attacks and their frequency decreased following acupuncture therapy. In conclusion, while cortisone is the first preference in the treatment of temporal arteritis, we think that acupuncture aimed at the cause of accompanying symptoms can also be useful. Keywords: acupuncture, headache, temporal arteritis, migraine